Factors Affecting Individual Taxpayer Compliance with Practice Self Assessment System as Intervening Variable - Yuswar Z. Basri, Sabaruddin; Dwimulyani, Susi (Journal of Entrepreneurship, Business and Economics, 2018)
The purpose of this study is to obtain empirical evidence whether perceptions of corruption, fiscal services and tax sanctions affect taxpayer compliance with the practice of self assessment system as intervening variable. The research design used is quantitative with primary data. Respondents in this study are financial managers, accounting managers and tax managers of companies registered in the MM2100 Industry area amounting to 219 people. Data analysis was performed using Sequential Equation Modeling (SEM) software - Lisrel 8.70 with a tolerable error rate of 5%. The results show that the direct influence of perceptions on corruption and fiscal services on taxpayer compliance can not be proven, but the perception of tax sanctions on compliance can be proven. The direct influence of perceptions on corruption, fiscal services and tax sanctions on the practice of self assessment system can be proven. The indirect influence of perceptions on corruption, fiscal services and tax sanctions on taxpayer compliance through intervening variables ie self assessment system practice can be proven. Research paper Keywords: Perception, corruption, fiscal services, tax sanction and self assessment system Reference to this paper should be made as follows: Basri, S. Y. Z. & Dwimulyani, S. (2018). Factors affecting Individual Taxpayer Compliance with Practice Self Assessment System as Intervening Variable, Journal of Entrepreneurship, Business and Economics , 6 (1), 116–143.